2017
DOI: 10.5530/jyp.2017.9.58
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study of tetraprenyltoluquinone, an anticancer compounds from Garcinia cowa Roxb

Abstract: Objective: To investigate the in vivo antitumor effect of TPTQ against H-460 lung cancer cell lines in nude mice. Materials and Methods: Female nude mice bearing H-460 tumor at size approximately 5 mm in diameter were treated with a single intraperitoneal dose 800 mg/kg of TPTQ. The vehicletreated (10% tween 80) animals were used as control group. The tumor size and mice body weight were measured for 14 days. Results: Single treatment of 800 mg/kg of TPTQ displayed moderate antitumor activity against H-460 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…All of the chemicals and reagents used were analytical grade. Reference standard TPTQ was provided from the previous studies [10].…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the chemicals and reagents used were analytical grade. Reference standard TPTQ was provided from the previous studies [10].…”
Section: Chemicalsmentioning
confidence: 99%
“…Two isolated compounds, cowanin and tetraprenyltoluquinone (TPTQ) revealed cytotoxic activity against T47D human breast cancer and H-460, respectively. Furthermore, cowanin could decrease cell mobility and stimulate cell cycle arrest on T47D cancer cells line [7,8,9,10].…”
Section: Introductionmentioning
confidence: 98%
“…Tetraprenyltoluquinone is a compound isolated from the hexane fraction of kandis acid bark (Garcinia cowa, Roxb) [14], which has been reported to have anticancer activity in vivo tested using mice. Administration of tetraprenyltoluquinone compound at a dose of 800 mg/Kg for 14 days in mice with H460 cells implanted subcutaneously in the right pelvis could slow tumor growth within five days of administration of the compound [15].…”
Section: Introductionmentioning
confidence: 99%
“…1) reported had a selective cytotoxic activity against small lung cancer [5]. The only in vivo study reported an antitumor activity by inhibiting tumor growth in H-460 tumor xenografted nude mice with dose at 800 mg/kg [6]. This compound also had a strong antiinflammatory activity againts NO [7], immunomodulatory, and safety against RAW 264.7 cell and leukocyte cell [8].…”
Section: Introductionmentioning
confidence: 99%